Introspective cosmopolitanism: The family in the Greek Weird Wave. Issue 1 (1st April 2020) - Eleftheriotis, Dimitris
This article reframes the critical discourse around the 'Greek Weird Wave' using an approach informed by theoretical work on cosmopolitanism. Focussing on Yorgos Lanthimos's Dogtooth (2009) and Athena-Rachel Tsangari's Attenberg (2010), the critical interpretation of the role of the family is radically rethought. I argue that the privileging of allegorical readings of the family in the Weird Wave films constitutes a form of critical denial of the deeply problematic and specifically Greek ways in which the family (dys)functions. I challenge the absolute and exclusive power that the Greek 'crisis' holds over interpretations and evaluations of Weird Wave films, which discursively displaces the problems of the family to broader sociopolitical frameworks. In reclaiming the importance of literal readings of the films, I reposition them as manifestations of a specific cosmopolitan disposition, that of introspection, a process of self-examination that overcomes denial. In turn, the critical reframing of the films outlines the contours of a complex agonistics of introspective cosmopolitanism, an inward investigative disposition that is dialectically linked to cosmopolitan positioning. Jean François Lyotard's 1989 theorization of the oikos (home/house) provides a conceptual model for understanding the family (oikogeneia), which, in its Greek specificities, is central to the films under discussion.